2020
DOI: 10.3390/ijerph17207458
|View full text |Cite|
|
Sign up to set email alerts
|

Survival and Estimation of Direct Medical Costs of Hospitalized COVID-19 Patients in the Kingdom of Saudi Arabia

Abstract: Objectives: Assess the survival of hospitalized coronavirus disease 2019 (COVID-19) patients across age groups, sex, use of mechanical ventilators (MVs), nationality, and intensive care unit (ICU) admission in the Kingdom of Saudi Arabia. Methods: Data were retrieved from the Saudi Ministry of Health (MoH) between 1 March and 29 May 2020. Kaplan–Meier (KM) analyses and multiple Cox proportional-hazards regression were conducted to assess the survival of hospitalized COVID-19 patients from hospital admission to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
72
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 32 publications
9
72
1
6
Order By: Relevance
“…We report an average hospital admission cost of US$12,637.42, which is almost double China's published cost of US$6,827 from 70 empirically observed cases [14] but is similar to the US$12,547 reported in a study from Saudi Arabia. [15] However, when interpreting average admission costs, the disease severity profile of the population must be considered. In our study, the average cost of admission was US$20,002.80 for the hospitalized severe cases admitted to ICU [12] (who accounted for 51.7%) and US$4,839.57 for the other cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We report an average hospital admission cost of US$12,637.42, which is almost double China's published cost of US$6,827 from 70 empirically observed cases [14] but is similar to the US$12,547 reported in a study from Saudi Arabia. [15] However, when interpreting average admission costs, the disease severity profile of the population must be considered. In our study, the average cost of admission was US$20,002.80 for the hospitalized severe cases admitted to ICU [12] (who accounted for 51.7%) and US$4,839.57 for the other cases.…”
Section: Discussionmentioning
confidence: 99%
“…The average hospital admission cost of US$12,637.42 is similar to the model means of US$12,264, which was predicted using data for severe pneumonia hospitalizations due to H1N1 in the USA, [21] and US$12,947, which was based on MERS-CoV data from Saudi Arabia. [15] The reported hospital costs of seasonal influenza infections are higher; a study described them to be US$34,743 for patients aged between 20 and 64 years. [22] Data about other epidemics showed that the cost of treatment of patients with pertussis ranged from $412-$555 [23] and estimated the cost for treating 11 patients with Ebola virus disease during the 2014 outbreak in West Africa to be US$1.2 million in a treatment center in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the authors in [51] estimated the statistic COVID-19 cases in Saudi Arabia, where the ratio of patients for the general medical ward was at 84.39%, with an average cost of US$11,385.18 per patient, and the percentage of those entering into intensive care unit was 15.61%, and its mean cost per patient was US$ 21,173.22. Additionally, a few related reports estimated the average cost for a hospitalized case as US$2.395 in China [52] , US$ 4,633.43 in India [53] , US$10,000 in Canada [40] , and US$ 12,916.31 in Sweden [54] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…We will assume that the potential cost for the critical case is US$ 21,173.22 as in the study [51] , the potential cost for the severe case is US$ 3045, and the potential cost for mild illness is US$96 such as in the study [45] . We calculate the percentages for these categories based on the real data from GitHub repository [55] .…”
Section: The Modelmentioning
confidence: 99%
“…There is an error in the title. The correct title of the article [ 1 ] is “Survival and Estimation of Direct Medical Costs of Hospitalized COVID-19 Patients in the Kingdom of Saudi Arabia”. We apologize for this error and state that the scientific conclusions are unaffected.…”
mentioning
confidence: 99%